PENGARUH TOTAL QUALITY MANAGEMENT DAN KEADILAN PROSEDURAL (PROCEDURAL JUSTICE) TERHADAP KINERJA KARYAWAN DI PT. LAMONGAN GAS LESTARI KABUPATEN LAMONGAN - Miftahul Huda; Moh. Azus Shony Azar (LPPM UNISDA, 2019)
Human resources are important in a company Therefore, it is necessary to have good human resource management to support the achievement of the objectives of the company by implementing Total Quality Management and Procedural Fairness to employees. This research to determine and analyze how much Total Quality Management and Procedural Fairness on Employee Performance. The sampling technique used is field research using saturated samples. The samples of this study were 34 samples, employees who worked at PT. Lamongan Gas Lestari Lamongan Regency which then becomes the respondent and fills in the questionnaire provided by the author. Based on questionnaire data that has been processed with the help of the SPSS 23.0 application and has been tested for validity and reliability, it can be stated that all of the data is valid and reliable. Then based on the results of the study show based on the F test states that there is an effect of Total Quality Management, Procedural Justice simultaneously on employee performance of 30,660, t test stated that the variable Total Quality Management of 2.952 and Procedural Justice of 3.420 is the dominant variable in influencing employee performance. Based on the coefficient of determination test it can be seen that the R2 value of 66.4 means that the influence of Total Quality Management, Procedural Justice and employee performance is 66.4%, the remaining 33.6% is influenced by other factors outside this research variable.